Innovative catalytic converter from FeCrAl material coated by γ-Al2O3 and NiCr for increasing thermal stability at high temperature operation - Dafit Feriyanto; Zaenudin Zaenudin (Politeknik Negeri Lhokseumawe, 2023)
The transportation sector plays a significant role in air pollution and the greenhouse gas effect. Therefore, the innovation of exhaust system component needs to be conducted to reduce those issues. The most effective technology is by using a catalytic converter have main function is to convert the exhaust emission. The main problemfaced by the previous study is the high degradation of FeCrAl material up to 19.58 mg at 1000oC. Therefore, the objective of this study is to develop a catalytic converter that has high thermal stability. This research was conducted by various coating processes which is Ultrasonic Bath (UB) and ultrasonic bath combined with electroplating (UB+EL) with parameters of UB consisting of frequency of 35 kHz, various holding times of 1, 1.5, 2, 2.5 and 3 hours while parameters in electroplating process are current density of 8 A/dm2 and holding time of 15, 30, 45, 60 and 75 minutes. That process was followed by a drying process at 60oC for 12 hours. The materials used in this research are FeCrAl as substrate, Ni as catalyst, γ-Al2O3 and Cr as wash-coat material. The results show that coating process coating process of γ-Al2O3 and NiCr on FeCrAl substrate succeeded in analysis proved by microstructure and composition analysis. The appropriate coating is shown by UB+EL 30 minute with the highest thermal stability of 2.85mg and reaction point is 0.07 mg/minute. Several compounds developed during the coating process such as in UB process develop FeCrAl, FeO, γ-Al2O3 and FeCr2O3 compounds and in the UB+EL process FeCrAl, FeO, γ-Al2O3, FeCr2O3, NiO, NaO2, NiAl2O4 and NiCr2O4 compounds. Therefore, UB+EL 30 minutes is the most parameters that are recommended to be applied due to the lowest mass degradation and more compounds.The transportation sector plays a significant role in air pollution and the greenhouse gas effect. Therefore, the innovation of exhaust system component needs to be conducted to reduce those issues. The most effective technology is by using a catalytic converter have main function is to convert the exhaust emission. The main problemfaced by the previous study is the high degradation of FeCrAl material up to 19.58 mg at 1000oC. Therefore, the objective of this study is to develop a catalytic converter that has high thermal stability. This research was conducted by various coating processes which is Ultrasonic Bath (UB) and ultrasonic bath combined with electroplating (UB+EL) with parameters of UB consisting of frequency of 35 kHz, various holding times of 1, 1.5, 2, 2.5 and 3 hours while parameters in electroplating process are current density of 8 A/dm2 and holding time of 15, 30, 45, 60 and 75 minutes. That process was followed by a drying process at 60oC for 12 hours. The materials used in this research are FeCrAl as substrate, Ni as catalyst, γ-Al2O3 and Cr as wash-coat material. The results show that coating process coating process of γ-Al2O3 and NiCr on FeCrAl substrate succeeded in analysis proved by microstructure and composition analysis. The appropriate coating is shown by UB+EL 30 minute with the highest thermal stability of 2.85mg and reaction point is 0.07 mg/minute. Several compounds developed during the coating process such as in UB process develop FeCrAl, FeO, γ-Al2O3 and FeCr2O3 compounds and in the UB+EL process FeCrAl, FeO, γ-Al2O3, FeCr2O3, NiO, NaO2, NiAl2O4 and NiCr2O4 compounds. Therefore, UB+EL 30 minutes is the most parameters that are recommended to be applied due to the lowest mass degradation and more compounds.